Impacts of arbuscular mycorrhizal and Trichoderma viride on enhancing physicochemical properties and triggering defense mechanisms of tomato plants challenged with potato virus Y - Aseel, Dalia Gamil; Ibrahim, Omar M.; Elbeaino, Toufic; Al-Askar, Abdulaziz A.; Abdelkhalek, Ahmed (Frontiers in Plant Science, 2025)
The utilization of arbuscular mycorrhizal fungi (AMF) and Trichoderma spp. correlates with improved plant nutrition and the stimulation of systemic plant defenses in response to pathogen challenges. Nonetheless, studies examining the effects of AMF colonization and the foliar application of the Trichoderma viride isolate Tvd44 on viral infection are limited. By analyzing the phenotypic, biochemical, and transcriptional expression of eleven defense genes, we investigated the effects of AMF colonization, foliar application of Tvd44, and their combined (dual) application on tomato plants challenged with potato virus Y. Interestingly, the dual application significantly suppressed viral symptoms and decreased viral accumulation levels, disease incidence, and disease severity by 88.1%, 40%, and 53.4%, respectively. Furthermore, both single and dual treatments significantly enhanced the activity of antioxidant enzymes, chlorophyll concentration, and macronutrient levels in the tomato tissues. In the realm of transcriptional analyses, the CHS gene served as a master key in understanding the physiological and pathway relationships among various genes (F3’H, HQT, C3H, GST, JERF, CHI, WRKY-1, WRKY-19, FLS, and F3H) involved in plant defense. These results suggest a sophisticated network of interactions that governs multiple facets of plant defense responses, encompassing the biosynthesis of flavonoids and other secondary metabolites, as well as the activation of transcription factors related to defense mechanisms. The obtained data indicate that AMF colonization and T. viride foliar spraying enhance tomato resistance to PVY by activating defense systems, thereby affecting viral replication. This finding highlights the significance of AMF and T. viride within the ecosystem and their crucial role in managing plant viruses.